STRENGTHENING NATIONALITY INSIGHT WITH GEO-LITERACY - Syafrida Selfiardy (GeoEco, 2020)
The nationality insight should be owned by all Indonesian citizens. This insight is identical with civics knowledge. Besides, not only by studying civics knowledge anyone can improve their nationality insight, but also from other knowledge, such as by learning geography science. Understanding the environment is one of the scopes in geography science. Understanding the environment can possibbly to increase the nationality insight. This research aims to applying geo-literacy as a study method, so the student can improve their ability to understand the earth. The subject of this research is the 4th semester student of Geography Education Department, Faculty of Social Science Universitas Negeri Manado. Analyzing data is based on the calculation of the percentage of results of filling out questionnaires by respondents. The questionnaires formed by the author from literature study from the syntax of geo-literacy method (from the National Geographic Magazine) combine with the indicator of nationalism in the document of nationality by Lembaga Administrasi Negara Republik Indonesia. By applying geo-literacy as a study method in geography education, the majority of students strongly agree that geo-literacy has the ability to strenghtening student’s knowledge to know the world (by applying geographical approach) and make the best decision for the environment.